PEMBELAJARAN KOOPERATIF MELALUI TEKNIK DUTI-DUTA DALAM MENINGKATKAN KEMAMPUAN MENULIS ARGUMENTASI - Diena San Fauziya (Sekolah Pascasarjana Universitas Pendidikan Indonesia, 2016)
Factors that reduce the ability of students to write the argument for their demands of authors presented facts and his opinions on an issue. For the purpose of this research to improve students' writing skills argumentation. Role model of learning is very important in order to achieve that goal. Cooperative learning through techniques Duti-Duta is a solution. The method used is classroom action research (PTK) consisting of two cycles. Based on the analysis cycle I and II, students' ability in writing argumentation has increased significantly, amounting to 89.29% of students were able to achieve a better assessment categories. It can be concluded that the use of cooperative learning model through engineering Duti-Duta is able to improve students' writing argumentation. Keywords: learning, cooperative, improvement, writing, argument